A DEIXIS ANALYSIS OF THE NOVEL LAKON BY ARDINI PANGASTUTI BN - Tri Pertika Wulandari (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2026)
The purpose of this study is to identify the types of deictics in the novel Lakon by Ardini Pangastuti Bn through a pragmatic analysis using George Yule’s theory. This is a qualitative study in the field of literature. The primary data sources in this study consist of all forms of deictics, including words, phrases, and clitics found in the novel Lakon, while the secondary data sources consist of books and articles that support the analysis. Data collection techniques include literature review, observation, and note-taking. The data analysis technique is content analysis, which involves a comprehensive examination of the text, while data presentation is conducted informally. The results of the study reveal three types of deictics in the novel Lakon, namely: 1) personal deictics, including: a) free-form first-person singular deictics, such as The results of the study reveal three types of deictics in the novel Lakon, namely: 1) personal deictics, including: a) free-form first-person singular deictics, such as aku and kula; right-bound first-person singular deictics, namely –ku; and free-form first-person plural deictics, such as awake dhewe. b) free forms of second-person singular deictics include kowe, awakmu, sampeyan, panjenengan, and njenengan; the right-bound form of second-person singular deictics is –mu; c) free forms of third-person singular deictics include dheweke; the right-bound form of third-person singular deictics is –e; 2) Spatial deictics found include the forms kene and mrene, which indicate a place close to the speaker; the forms kono and mriku, which indicate a place somewhat distant from the speaker; and the forms mrana and kana, which indicate a place far from the speaker; 3) Temporal deictics found include the form saiki, which refers to the present time. Deixis indicating the past or a time that has already occurred uses the forms semana, mbiyen, and biyen.